Agent Oriented Software Engineering: Why and How - Padgham, Lin; Thangarajah, John (VNU Journal of Science: Natural Sciences and Technology, 2011)
Abstract . This paper introduces the concept of agents, and agent systems, and then motivates why developers may want to use this technology for building complex software systems. It describes a particular approach to Agent Software Engineering, the Prometheus methodology, and the associated Prometheus Design Tool.  The paper concludes with a discussion of some of the current trends in Agent Oriented Software Engineering.